Energy deposition calculation by Monte Carlo simulation in irradiation of electric cables by electron beam. (September 2021) - Jung, Seung-Tae; Pyo, Seong-Hwan; Kang, Won-Gu; Kim, Yu-Ri; Kim, Jin-Kyu; Kang, Chang M.; Nho, Young-Chang; Park, Jong-Seok
Abstract: The reason for crosslinking the insulation polymer in wire and cable by radiation is to improve their performance at an elevated temperature, the chemical resistance, toughness and abrasion resistance in use. The quality of products made by radiation processing depends not only on the absorbed dose but also on homogenuity of dose distribution especially in circular objects like cables which have different density in conductor and insulation part, respectively. It is important to optimize crosslinking processes for reducing the operation cost while sustaining suitable quality of the final product. The computer simulation method becomes a very useful tool for optimizing process, providing essential information in a short time and reducing cost comparing with the conventional method based on experimental dosimetry. The application of several Monte Carlo codes for electron and photon transport and the advances in computing systems, make possible to accomplish dosimetry tasks by numerical simulation. With increased computing speed and decreasing hardware cost, it is expected that Monte Carlo based electron dose calculation algorithms will become available for routine electron beam dosimetry. We have developed the EBSCANmc (simulator program) in order to simulate and study the crosslinking of electric cables. EBSCANmc employs the MCNP (Monte Carlo N-Particle) 6.2 code, which is a general purpose Monte Carlo particle transport code. The computer simulation of the dose distributions in electric cables was performed for various process parameters, namely the level of electron beam energy, irradiation positions, the density of cable insulator, and backscattering. The results of computer simulation are compared with experimental data using the CTA film dosimeter. Highlights: The computer simulator for the dose distributions in electric cables was developed. Energy deposition in polymeric materials used as sheath layer and insulation layer was calculated. The methods to increase the dose uniformity were studied. The computer simulation was compared with experimental data.